Evolutionary tradeoffs and the geometry of gene expression space - Alon, Uri (Henry Stewart Talks, 2014)
Organisms, tissues and molecules often need to perform multiple tasks, Usually no phenotype can be optimal at all tasks at once which leads to a fundamental tradeoff, We study this using the concept of Pareto optimality from engineering and economics, Tradeoffs lead to an unexpected simplicity in the range of optimal phenotypes; they fall on low dimensional shapes in trait space such as lines, triangles and tetrahedrons, At the vertices of these polygons are phenotypes that specialize at a single task, We demonstrate this using data from animal and fossil morphology, bacterial gene expression and other biological systems.